Leprechaun on the Loose - Kelleher, Annette; Illustrated by Phillip Morrison (Ireland The O'Brien Press Ltd)
Biddy Blatherskate is fed up with wet weather and minding her father's gold. She does a deal with an Australian boy, Corey - her father's gold for Corey's passport! But this can only lead to trouble.
Include Illustration
Keywords: Leprechauns